Let f and s be the ages of the father and the son. We have
![\begin{cases}f+s=42\\fs=185\end{cases}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/im07tnie50lguh3j11qthd03cl4gir6s8j.png)
From the first equation we derive
![f=42-s](https://img.qammunity.org/2020/formulas/mathematics/middle-school/org9zuwf7dqqxn0jtvoya5ynklq6i7178w.png)
Substitute this expression for f in the second equation and we have
![(42-s)s=185 \iff -s^2+42s-185=0 \iff s^2-42s+185=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o8knapljv3rd2trokdjqg8jsflfdh2mdu7.png)
The solutions to this equation are s=5 or s=37
Since the sum of the ages must be 42, the solutions would imply
![s=5 \implies f=37,\quad s=37\implies f=5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pdgpadngsl21olidrhwbktpu1yvfvntey2.png)
We can only accept the first solution, since the second would imply a son older than his father!